PERANCANGAN APLIKASI ELECTRONIC SUPPLY CHAIN MANAGEMENT PADA PT RIMAU SHIPPING BERBASIS WEB - Ranawijaya, Daniel; Rusdi, Zyad (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
The company will improve competitiveness through adjustments products, high quality, cost reduction, and velocity distribution then must pay attention supply chain (supply chain). chain management supply (supply chain management) is material procurement and integration activities services, conversion to intermediate goods and end products, as well as delivery to customers. These activities include activities its purchasing and outsourcing, plus other functions which is important for the relationship between supplier with distributors. The main goal of the SCM is delivery of the product appropriately time in order to satisfy consumers, reducing costs, improving all the results from all supply chain (not just one company), reduce the time, focus activities planning and distribution. implementation of supply chain management in the future as it is suitable applied, because this system has advantages where able to manage the flow of goods or products in a supply chain. Key words supply chain management, supply chain